Do We Know the Minimal Clinically Important Difference (MCID) for COPD Exacerbations?. (21st March 2013) - Chapman, Kenneth R.; Bergeron, Celine; Bhutani, Mohit; Bourbeau, Jean; Grossman, Ronald F.; Hernandez, Paul; McIvor, R. Andrew; Mayers, Irvin
Abstract Frequent exacerbations of COPD are associated with accelerated loss of lung function, declining health status, increased mortality, and increased health care costs. Thus, a key objective in the management of COPD is preventing exacerbations or at least reducing their number and severity. When new interventions are examined, their value is sometimes assessed in reference to the minimal clinically important difference (MCID), a theoretical construct that may be defined and estimated numerically in several different ways. There have been limited attempts to calculate the MCID for COPD exacerbations but a figure of 20% reduction in exacerbation frequency is occasionally cited as the "established" MCID from a single manuscript reviewing six clinical trials. Our review suggests that defining and calculating the MCID for COPD exacerbations is problematic, not only because the methodology around developing endpoints for MCIDs is inconsistent, but because the impact of exacerbation reduction is likely to be influenced dramatically by the definitions of exacerbation severity used and the population's baseline status. Reference to current literature shows that at least one other estimate for exacerbation MCID as low as 4%. MCID is sometimes estimated by expert consensus; a review of articles used to shape COPD guidelines shows frequent reference to articles in which interventions yielded exacerbation differences as low as 11%. We find no evidence of an established MCID but suggest that interventions reducing exacerbations by as little as 11% appear to be regarded widely as clinically important.